Implementation of Lean Six Sigma to Improve Logistic Operational Performance in the Industrial Boiler Manufacturing - Simatupang, Remon; Nugroho, Rosalendro Eddy (Indikator: Jurnal Ilmiah Manajemen dan Bisnis, 2025)
Logistic operational is the heart of supply chain management that must always exist simultaneously to maintain the sustainability of a business operation in an era of high competitiveness by continuing to provide positive impacts on people and the planet. This is what prompted the Author to conduct a case study on a multinational company that produces industrial boilers and their equipment. The Lean Six Sigma methodology used has proven effective in finding the root of the problem, measuring achievements, analyzing data, preparing improvement steps and controlling each improvement process to ensure continuous improvement. Through joint efforts in the Focus Group Discussion forum, this study has proven to have helped the company to improve its previous condition, where logistics operational costs were very high due to the high cost of the inward process and had an impact on the high carbon footprint produced by transportation equipment, especially those related to the outward process. Improvement in logistics operational performance in the inward and outward processes that resulted cost saving in six months of implementing the improvements. This achievement not only provides financial benefits for the organization, but also impacting to minimize carbon footprint.